Exploring the bidirectional causality between neuroticism and frailty: a Mendelian randomization analysis - Yuhang Xing; Rui Pu; Mengdie Fu; Zhikang Wang; Zhen Wang; Xiaopeng Shang; Guoli Yang; Zhiwei Jiang (Hereditas)
Abstract Background Epidemiological studies have confirmed the relationship between personality trait neuroticism and physical health. However, the relationship between neuroticism and frailty remains unconfirmed. This study employed a bi-directional two-sample Mendelian randomization (MR) approach to investigate the causal relationship between neuroticism and frailty. Methods The neuroticism genome-wide association study (GWAS) data from the UK Biobank contained twelve neuroticism-related traits with 489,212 participants. The genetic frailty index data were extracted from the UK Biobank and Swedish TwinGene, involving 175,226 individuals. Independent genetic variants associated with neuroticism and frailty were selected as instrumental variables. Inverse variance weighted (IVW), MR-Egger, weighted median, weighted mode, and MR-PRESSO were mainly used for MR analysis. Results The MR analysis showed a positive causal relationship between neuroticism and the risk of frailty (odds ratio (OR) = 1.627, 95% confidence interval (CI) = 1.538–1.722, P < 0.001). In the reverse direction, frailty had a causal effect on a higher risk of neuroticism (OR = 1.270, 95% CI = 1.173–1.375, P < 0.001). Steiger tests indicated that reverse causation did not bias the identified causal relationships. Conclusions Our study provides genetic evidence suggesting a bi-directional causal relationship between frailty and neuroticism. In this bi-directional MR study, there were positive causal relationships between neuroticism-related phenotypes and frailty, and in the reverse direction, frailty was also positively correlated with neuroticism.